May Ingestion of Leachate from Decomposed Corpses Cause Appendicitis? A Case Report - Maurício Domingues-Ferreira; Pedro Saddi-Rosa; André Luis dos Santos (Case Reports in Medicine)
The general consensus is that appendicitis is basically provoked by fecaliths or lymphoid hyperplasic obstruction. Several studies based on histological diagnosis have not confirmed this hypothesis. On the contrary, obstruction has been proved in only a minority of cases. Diverse infections by parasites, bacteria, fungus, and noninfective agents have been associated with appendicitis in the medical literature. We describe a firefighter, who ingested a small quantity of leachate from decomposing corpses while working and developed enteritis a few hours later, which lasted several days and evolved to appendicitis. This case raises the possibility that the high quantity of bacteria concentration present in the leachate could have provoked enteritis and the subsequent appendicitis due to a direct effect of the bacteria on the appendix.